1991
DOI: 10.3382/ps.0702433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fructooligosaccharide on Salmonella Colonization of the Chicken Intestine

Abstract: The influence of fructooligosaccharide (FOS) on the ability of Salmonella typhimurium to grow and colonize the gut of chickens was investigated. In vitro studies showed that Salmonella did not grow when FOS was the sole carbon source. When FOS was fed to chicks at the .375% level, little influence on Salmonella colonization was observed. At the .75% level, 12% fewer FOS-fed birds were colonized with Salmonella compared with control birds. When chicks given a partially protective competitive exclusion (CE) cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
2
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(105 citation statements)
references
References 17 publications
4
93
2
6
Order By: Relevance
“…It is demonstrated that the control of Salmonella is achieved by low pH and high level of volatile fatty acids in broiler caeca content (Corrier et al, 1990a(Corrier et al, , 1990b. In vitro studies showed that Salmonella typhimurium did not grow when FOS was the sole carbon source (Bailey et al, 1991), therefore feeding oligofructose may be a practical strategy for controlling Salmonella in chicks. However, studies conducted on broilers to examine the potential effect of dietary fructans on Salmonella colonization of the chicken intestine and contamination of processed broiler carcasses are not unambiguous.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
See 3 more Smart Citations
“…It is demonstrated that the control of Salmonella is achieved by low pH and high level of volatile fatty acids in broiler caeca content (Corrier et al, 1990a(Corrier et al, , 1990b. In vitro studies showed that Salmonella typhimurium did not grow when FOS was the sole carbon source (Bailey et al, 1991), therefore feeding oligofructose may be a practical strategy for controlling Salmonella in chicks. However, studies conducted on broilers to examine the potential effect of dietary fructans on Salmonella colonization of the chicken intestine and contamination of processed broiler carcasses are not unambiguous.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
“…Moreover, there was no consistent effect of caecal pH observed in chicks fed diets with crude and refined FOS on Salmonella infection. Bailey et al (1991) reported that 0.375% FOS in the diet was insufficient to affect caeca colonization of Salmonella typhimurium, whereas 0.75% level decreased by 12% the number of birds that were colonized with Salmonella compared with control broilers. This effect was much more pronounced when chickens were stressed by feed and water deprivation.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
See 2 more Smart Citations
“…nutrients designed to influence the intestinal flora in a positive way may also be used but there is limited information on their effect on Salmonella colonisation in the field. In experimental "in vivo" trials, protective effects of fructooligosaccharides have been shown with respect to Salmonella colonization of the chicken intestine (Bailey et al, 1991). large country differences in the resistance prevalences and patterns were observed.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%